Efektivitas Terapi Thought Stopping Terhadap Fatigue (Kelelahan) Pada Mahasiswa Program Studi S1 Keperawatan Institut Kesehatan Payung Negeri Pekanbaru - Ershanda Razalianti; Desti Puswati; Fitri Dyna; Afrida Sriyani Harahap (Journal of Innovative and Creativity, 2026)
Academic fatigue is a condition of physical, mental, and emotional exhaustion experienced by students as a result of continuous academic demands and accompanying psychological pressure. One strategy that can be applied to address this condition is psychological intervention, such as thought stopping therapy. Thought stopping is a technique used to regulate the negative thoughts that arise. This study aimed to determine whether thought stopping therapy is effective in reducing fatigue among undergraduate nursing students at the Institute of Health Sciences Payung Negeri Pekanbaru. This study employed a quantitative method with a quasi-experimental approach and a one-group pretest–posttest design. The study population consisted of all fourth-year students at the Institute of Health Sciences Payung Negeri Pekanbaru, with a total of 22 respondents selected using a random sampling technique. Data analysis was conducted using the Wilcoxon test. The results showed that thought stopping therapy was effective in reducing fatigue among undergraduate nursing students at the Institute of Health Sciences Payung Negeri Pekanbaru, with a p-value of 0.000 < 0.05. These findings suggest that thought stopping therapy can be used as an alternative psychological intervention to reduce fatigue and improve student well-being.